Managing their own affairs : the Australian deaf community in the 1920s and 1930s - Carty, Breda (Washington, DC : Gallaudet University Press, 2018)
Over de Australische dovengemeenschap in het beginvan de 20ste eeuw.
Includes bibliographical references (pages 241-249) and index.
Keywords: Deaf -- History -- 20th century -- Australia; Deaf -- Services for -- History -- 20th century -- Australia; Deaf -- Social conditions -- 20th century -- Australia